ANALISIS KORELASI KANONIK PADA HUBUNGAN ANTARA SOFT SKILLS TERHADAP PRESTASI BELAJAR MAHASISWA - JULIANINGSIH, NI PUTU; KENCANA, EKA N; SUKARSA, KOMANG GDE (E-Jurnal Matematika, 2019)
The purpose of this study is to know the relationship between soft skills and learning achievement using canonical correlation analysis and to find out the dominant dimensions of soft skills and learning achievement using confirmatory factor analysis. The data used are primary data obtained by distributing questionnaires. The sampling technique used was proportional to size sampling with the number of respondents as many as 150 respondents. The results of the study with canonical correlation analysis showed that soft skills with learning achievement had a close relationship with canonical correlation values ??of 0.70397. The results of the study with confirmatory factor analysis showed that the dominant dimensions of soft skills and learning achievement were flexibility with the percentage of the variance of 69.081% and cognitive percentage of the variance of 71.706%.